HUBUNGAN STRES KERJA TERHADAP KINERJA KARYAWAN PT RAFIKA TRANS INDONESIA KOTA CILEGON TAHUN 2023 - Ratu Wavia Nadiarta, (2023)
An organization may gain a lot from well-performed employees, including greater productivity, high-quality output, satisfied clients, and a strengthened brand identity. Performance can suffer from a number of variables, including job stress, environmental factors, organizational issues, and individual characteristics. This study intends to ascertain the impact of work stress factors on employee performance in connection to other variables such as age, gender, duration, workload, motivation, and income. This research is a quantitative study using a cross-sectional design with chi-square test analysis on a total population of 75 people. The research instrument used the IWPQ (Individual Work Performance Questionnaire), NASA-TLX and JSS (Job Stress Scale) questionnaires. According to the study's findings, there is a connection between employee performance and work-related stress (p=0.005, or=0.167), workload (p=0.022, or=3.000 and 0.800), working hours (p=0.050, or=0.316), and work motivation (p=0.015, or=0.242). There is no statistically significant correlation between employee performance and the variables age (p=0.270, or=3.143), gender (p=0.270, or=2.000), or income from work (p=0.477, or=0.662).. It is evident that there is a connection between workplace stress variables and worker performance. Companies may still help employees by offering psychological consultation services, enhancing employee welfare, paying attention to workload, and offering training to enhance staff performance.